2008
DOI: 10.1542/peds.2007-2767
|View full text |Cite
|
Sign up to set email alerts
|

Growth Characteristics of Infantile Hemangiomas: Implications for Management

Abstract: Most infantile hemangioma growth occurs before 5 months, yet 5 months was also the mean age at first visit to a specialist. Recognition of growth characteristics and factors that predict the need for follow-up could help aid in clinical decision-making. The first few weeks to months of life are a critical time in hemangioma growth. Infants with hemangiomas need close observation during this period, and those who need specialty care should be referred and seen as early as possible within this critical growth pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
515
2
27

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 597 publications
(554 citation statements)
references
References 26 publications
10
515
2
27
Order By: Relevance
“…Focal IHs are rarely present at birth and exhibit a characteristic growth phase typically up to the age of 9 months. 5 A gradual involution phase takes place over the subsequent 2 to 10 years 1,5 ; however, recently, Couto et al 6 suggested that most IHs do not substantially further improve after 3.5 years of age. Increasingly, nonselective b-blockers, including propranolol hydrochloride, have replaced or been used in conjunction with previously recommended treatments such as systemic corticosteroids and vincristine for the treatment of IHs to prevent ulceration and disfigurement and for systemic involvement.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Focal IHs are rarely present at birth and exhibit a characteristic growth phase typically up to the age of 9 months. 5 A gradual involution phase takes place over the subsequent 2 to 10 years 1,5 ; however, recently, Couto et al 6 suggested that most IHs do not substantially further improve after 3.5 years of age. Increasingly, nonselective b-blockers, including propranolol hydrochloride, have replaced or been used in conjunction with previously recommended treatments such as systemic corticosteroids and vincristine for the treatment of IHs to prevent ulceration and disfigurement and for systemic involvement.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Большинство ИГ локализуются в области головы и шеи (60%), реже -на туловище (25%) и на конеч-ностях (15%) [9].…”
Section: клиническая картинаunclassified
“…1 Typically they present shortly after birth, undergo a period of rapid proliferation, and then slowly involute over many years. 2,3 Although most are small cutaneous vascular malformations of the face, 4 they can also be large, disfiguring lesions with serious complications. Infants with large hemangiomas, especially those with a segmental distribution or hemangiomatosis, are at particular risk for extracutaneous complications.…”
Section: Introductionmentioning
confidence: 99%